PREDIKSI WAKTU KETAHANAN HIDUP DENGAN METODE PARTIAL LEAST SQUARE - KUSUMA, PANDE PUTU BUDI; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 2 No 1 (2013): E-Jurnal Matematika, 2013)
Coronary heart disease is caused due to an accumulation of fat on the inside walls of blood vessels of the heart (coronary arteries). The factors that had led to the occurrence of coronary heart disease is dominated by unhealthy lifestyle of patients, and the survival times of different patients. This research objective is to predict the survival time of patients with coronary heart disease by taking into account the explanatory variables were analyzed by the method of Partial Least Square (PLS).  PLS method is used to resolve the multiple regression analysis when the specific problems of multicollinearity and microarray data. The purpose of the PLS method is to predict the explanatory variables with multiple response variables so as to produce a more accurate predictive value.  The results of this research showed that the prediction of survival for the three samples of patients with coronary heart disease had an average of 13 days, with a RMSEP value (error value) was 1.526 which means that the results of this study are not much different from the predicted results in the field of medicine. This is consistent with the fact that the medical field suggests that the average survival for patients with coronary heart disease by 13 days.
Keywords: Survival; Coronary Heart Disease; Multicollinearity; Microarray Data; Partial Least Square